The success rate of trial of labour after caesarean section: does intrapartum epidural analgesia affect the outcomes? - Abdulwahab, Dalia F; Husin, Roziah; Jaafar Jas, Diyana; Awang, Mokhtar; Ismail, Rozihan (Willey Online Library, 2015)
Introduction: Neuraxial analgesia, is an effective treatment for labour pain, however this benefit was offset by possible association with increased risk of caesarean section and prolonged labour. The American college of Obstetrician and Gynaecologist recommended delaying the administration of epidural analgesia until cervical dilatation reach 4–5 cm, due to increase risk of CS up to 12 folds based on early studies Objective: To study the effect of epidural analgesia on the successes rates of vaginal birth in women undergoing trial of scar and labour outcome. Method: A prospective study conducted in Hospital Tengku Ampuan Afzan started June 2014, all consented women for trial of scar were counselled for either intrapartum epidural (study group) or control group were the women offered parenteral opioid or antanox, with the cervical dilatation of 3–4 cm. Result: Total of 42 ladies with the mean age of 30.7, mean gestational age was 39.4 (SD = 1.6) weeks, mean parity was 1.5, were recruited to this study from the labour room, divided into two equal groups, study group and control group. A sixty one point nine per cent (13/21) cases in the epidural group were induction of labour, versus 28.5% (6/21) cases from group. The mean duration of the first stage of labour was longer for the epidural group 6.3 (SD = 2.01) hrs, versus 4.4(SD = 2.68) hrs for the control groups but no statistical significant difference (P value 0.24). About 40.4% (17/42) cases had spontaneous vaginal delivery, with only 35% (6/17) cases from epidural group. Another 16.7% (7/42) cases had assisted delivery, four cases from epidural group. All indicated for fetal distress (FD) and only two cases indicated for prolong second stage both from the epidural group. The duration of AOCOG 2015 Abstract, Electronic Poster Presentations, Maternal Fetal Medicine © 2015 Japan Society of Obstetrics and Gynecology 127 the second stage was 39.9 minutes in the epidural group versus 22 minutes in the control group which is statistically significant. About 42.8% (18/42) cases delivered abdominally, the majority 61.1% (11/18) cases were from the epidural group (6 were indicated for poor progress, one failed induction and 4 for fetal distress), but was statistically not significant from control (P value 0.21). in the control group 3/7 cases were indicated for poor progress. None have maternal or neonatal complications. Conclusion: Epidural analgesia may be associated with prolonged labour, significantly prolonged second stage of labour, with lower rate of successful vaginal birth after CS, without increasing the complications rate. However large sample size is required to evaluate the statistical significance